Therapist-Led, Internet-Delivered Treatment for Early Child Social Anxiety: A Waitlist-Controlled Evaluation of the iCALM Telehealth Program. Issue 5 (September 2021) - Comer, Jonathan S.; Furr, Jami M.; del Busto, Cristina; Silva, Karina; Hong, Natalie; Poznanski, Bridget; Sanchez, Amanda; Cornacchio, Danielle; Herrera, Aileen; Coxe, Stefany; Miguel, Elizabeth; Georgiadis, Christopher; et al.
Highlights: Limited options are broadly available for families seeking treatment for early child social anxiety. The iCALM Telehealth Program uses videoconferencing to deliver therapist-led treatment for early child anxiety. Outcomes of a waitlist-controlled examination of the iCALM Telehealth Program are presented. iCALM led to improvements in child anxiety, impairment, and parental distress. Families with high levels of parental accommodation may particularly benefit from iCALM. Abstract: Despite recent advances in the treatment of early child social anxiety, the broad accessibility of brick-and-mortar services has been limited by traditional barriers to care, and more recently by new obstacles related to efforts to slow the spread of COVID-19. The present waitlist-controlled trial examined the preliminary efficacy of a family-based behavioral parenting intervention (i.e., the iCALM Telehealth Program) that draws on Parent-Child Interaction Therapy and videoconferencing to remotely deliver clinician-led care for anxiety in early childhood. Young children (3–8 years) with a diagnosis of social anxiety disorder ( N = 40; 65% from ethnic/racial minority backgrounds) were randomly assigned to iCALM or waitlist. Intent-to-treat analyses found that at post, independent evaluators classified roughly half of the iCALM-treated children, but only 6% of waitlist children, as "Responders" (Wald test = 4.51; p = .03). By Post, iCALM led to significantly greater reductions than waitlist in child anxiety symptoms, fear, discomfort, and anxiety-related social impairment, and also led to greater improvements in child soothability. By 6-month follow-up, the percentage of iCALM-treated children classified as "Responders" rose to roughly 60%. Exploratory moderation tests found iCALM was particularly effective in reducing life impairments and parental distress among families presenting with higher, relative to lower, levels of baseline parental accommodation. The present findings add to a growing body of research supporting the promise of technology-based strategies for broadening the portfolio of options for delivering clinician-led mental health services.